ANALISIS PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT FOOD AND BEVERAGES SERVICE DEPARTMENT TERHADAP MINAT BELI PRODUK FOOD AND BEVERAGES INTERCONTINENTAL JAKARTA PONDOK INDAH - Wibowo, Vincentius Bayu Tri; Sarudin, Rendy (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to provide a perspective on the effectiveness of implementing the concept of Customer Relationship Management for the company's business side, examine the benefits that guests can receive for purchasing products and services that have been made and explain whether or not there is a gap between expectations and reality felt by guests at InterContinental Jakarta Beautiful Cottage. The purposes of this study are 1) to provide an overview of the type and magnitude of the gap between guest expectations and the reality experienced in the field, 2) to determine the effectiveness of the role of Customer Relationship Management in building guest loyalty for the treatment or reward that has been provided by the company. The approach used in this study is the Quantitative Method, which obtains primary data from questionnaires as primary data and journals or books as secondary data. The results obtained in this study indicate that the dimensions used in Customer Relationship Management, namely Customer Orientation, Customer Relationship Management Organization and Knowledge Management are proven to be able to trigger Buying Interest which includes Attention, Interest, Desire and Action Dimensions of 43.4% for products Food and Beverages InterContinental Jakarta Pondok Indah. The conclusion of this study is that there are a number of expectations and reality gaps that cause the significance of the influence of the Customer Relationship Management Variable and the Purchase Intention Variable to be below 50% which indicates a not too strong influence. Besides that effectiveness of the type and amount of freebies to loyal members has a fairly good effectiveness, although it is not satisfactory.